Synthesis of Ce ions doped metal–organic framework for promoting catalytic H2 production from ammonia borane under visible light irradiation. Issue 27 (18th June 2015) - Wen, Meicheng; Kuwahara, Yasutaka; Mori, Kohsuke; Zhang, Dieqing; Li, Hexing; Yamashita, Hiromi
Abstract : Synthesis of Ce ion doped metal–organic framework for significantly promoting Pd catalyzed H2 production from ammonia borane under visible light irradiation. Abstract : A variety of physical properties such as optical, fluorescence, and guest absorption capacity integrated within hybrid MOF based materials may show synergetic effects for significantly enhancing the performance of many applications. In this study, new hybrid MOFs, cerium doped chromium based amine-functionalized metal–organic frameworks (CeMIL-101), were successfully synthesized for the first time, via hydrothermal treatment with the aim to enhance the photocatalytic activity of H2 production from ammonia borane (AB) under the assistance of visible light. The results analyzed by X-ray diffraction and X-ray adsorption near-edge structure strongly support the effective doping of Ce ions into the nodes of MIL-101. The catalytic activity of Pd/CeMIL-101 is remarkably higher than that of Pd/MIL-101 without Ce doping under visible light irradiation at ambient temperature. Pd/CeMIL-101 is highly efficient in generating the hydroxyl radicals and photo-excited charge transfer under visible light irradiation. Moreover, the presence of valence fluctuation of Ce 3+ /Ce 4+ was the main factor for reducing the recombination rate of photo-excited charges. This study may bring an effective strategy for the design and development of highly active hybrid materials for achieving high photocatalytic activity.